The Subtitusi Tepung Pisang Pada Pembuatan Nugget Puree Pisang Sebagai Alternatif Konsumsi Pangan (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2023)
The abundance of banana fruit has not been widely utilized into processed food. One way that can be done is to utilize it into local food ingredients, as raw material in making frozen food banana puree nuggets. Food diversification can increase public awareness about the importance of local ingredients as alternative food. This study aims to find a formula, and public acceptance of banana puree nuggets substituted with banana flour (Musa paradisiaca L.) and wheat flour to get the best formulation in terms of color, taste, aroma and texture. The percentage of banana flour used was 50%, 40%, 30%, 20%, 10% and control. The research method used was the experimental method using a randomized completely design (RCD) arranged in a non-factorial manner with the treatment factor of the ratio between banana flour and wheat flour consisting of five treatment factors and repeated three times. The parameters observed in this study were organoleptic test (Hedonic Test) conducted by 25 panelists from the general public, including visual (color), olfactory (aroma), gustatory (taste), and texture. The results showed that banana puree nuggets substituted with banana flour (Musa paradisiaca) were acceptable to the panelists with an overall score of 6.52, so banana flour (Musa paradisiaca) can be used as a substitute in making banana puree nuggets and supporting local food diversification. This invention can help increase public understanding of the importance of utilizing local food ingredients, such as bananas, in food product innovation.